Determinant factors that influence tourists to travel as backpackers in Malaysia - Abdul Rusman Hassanul Basri; Adlina Sharuddin; Muhammad Haikal Mohamad Fahimi; Nesha Manivannan (2021)
Tourism is the fastest growing industry in the world. This study would explore the motivation factors that influence tourists to travel as backpackers in Malaysia. Backpackers is a type of travellers that travel with his or her own decision without using the tour guide services, without using travel agencies as intermediaries and backpackers is the most independent traveller. As backpackers, risk always be an issue but their motivation would help them to keep travelling. This study would examine the relationship between push factors with motivation to be backpacker’s travellers among tourist in Malaysia, to examine the relationship between pull factors with motivation to be backpacker’s traveller among tourist in Malaysia and to determine the most influence factors that motivate tourist to be backpacker’s traveller in Malaysia. The quantitative method being used which is by using questionnaires through Google Form and 218 respondents were administrated among random respondent with backpackers travelling experience. The questionnaire consisted of 45 questions and divided into three sections that is section A, section B and section C. The data has been collected and analysed by using SPSS. The finalized result shown that both push factors and pull factors are related with respect to motivation to be backpacker’s travellers among tourist in Malaysia. The most influence factors that motivate tourist in Malaysia to travel as backpacker’s traveller in Malaysia is pull factors. It is recommended to emphasize the need for a more detailed division of backpackers in order to identify their interest and preferences. By understanding the characteristics of backpackers and investigating their travel motivations, the responsible organization would have the chance to cater to the demands of backpackers who have made a crucial contribution to the travel industry.